Evaluation of differences in the performance strategies of top and bottom basketball teams utilizing rank-sum ratio comprehensive - Wenping Sun; Wenping Sun; ChenSoon Chee; LianYee Kok; FongPeng Lim; Shamsulariffin Samsudin (Frontiers Media S.A., 2022)
IntroductionThis study aimed to explore common characteristics among top basketball teams, differentiate attacking and defensive performance between top and bottom teams, and correlate attacking and defensive performance with final competition rankings during the 2019 Men's Basketball World Cup, as well as to determine the relationship between performance indicators and the attacking and defensive performance. In addition, the study aimed to determine the attacking and defensive level of the top and bottom eight teams and find their existing problems and shortcomings, to further improve their competitive basketball strength, and also provided valid and reliable information for coaches to conduct targeted training in the future.MethodsThe rank-sum ratio (RSR) was employed to evaluate the attack, defense, and overall attacking and defensive performance between the top and bottom teams during the 2019 Men's Basketball World Cup. Additionally, an independent sample T-test was conducted to test the difference in performance indicators of attack and defense between the top eight and bottom eight teams. Spearman Rho Correlation was conducted to determine the relationship between the attacking and defensive RSR value and the final competition ranking at the 0.05 confidence level. Pearson Correlation was employed to test the relationship between the performance indicators and the attacking and defensive RSR value at the 0.05 confidence level. According to Spearman and Pearson Correlation, the indicators which contributed most to the attacking and defensive performance, as well as the correlation between attack and defense and the final ranking, can thus be determined.ResultsThe results showed that the attacking performance of the top eight teams was far better than the bottom eight teams in terms of average points (p = 0.000), 2-point shoot percentage (p = 0.001), 3-point shoot percentage (p = 0.003), free throw percentage (p = 0.001), turnovers (p = 0.012), and assists (p = 0.000), and there was a significant difference (p < 0.05). However, second attack (p = 0.484), fast-break (p = 0.174), and offensive rebounds (p = 0.261) showed no significant difference between the two cohorts (P > 0.05), and the offensive rebounds of the bottom eight teams were better than the top eight teams. Additionally, there was a large gap between the top eight teams and the bottom eight teams in lost points (p = 0.001) and defensive rebounds (p = 0.000), with a very significant difference (p < 0.01). However, steals (p = 0.760), blocks (p = 0.166), and fouls (p = 0.686) had no significant difference between the two cohorts (P > 0.05). Additionally, there was a very significant difference between attack RSR (p = 0.000), defense RSR (p = 0.006), and the overall attack-defense RSR (p = 0.000) of the top eight and bottom eight teams (p < 0.01), and most top teams focused on developing both attack and defense and paid attention to improve the overall attacking and defensive ability. Moreover, there was a significant relationship between the overall attack-defense performance and assists (p = 0.832), rebounds (p = 0.762), turnovers (p = 0.702), 2-point shoot percentage (p = 0.704), defensive rebounds (p = 0.809), fast-break points (p = 0.577), blocks (p = 0.600), and free throw percentage (p = 0.575).ConclusionsThis study showed that the top basketball teams focused on developing both attack and defense, and have the common characteristics of strong attack and defense. Whether it was the attack, defense, or overall attacking and defensive ability, there was a significant relationship with the final ranking. Additionally, this study showed that there were very significant differences in both attacking and defensive abilities between the top eight and bottom eight teams, as well as highlighted their respective advantages and disadvantages in attacking and defensive indicators. Besides that, this study found that performance indicators such as assists, defensive rebounds, 2P%, turnovers, FT%, fast-breaks, and blocks were the main factors that distinguish the top and bottom teams, and they had a significant relationship with overall attacking and defensive performance. The above information allows coaches and players to learn the latest developments in competitive basketball, as well as their advantages and disadvantages, to help them organize targeted training in the future.